If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(x + 2) + 3 = 6x + -3(-4 + x) Reorder the terms: 3(2 + x) + 3 = 6x + -3(-4 + x) (2 * 3 + x * 3) + 3 = 6x + -3(-4 + x) (6 + 3x) + 3 = 6x + -3(-4 + x) Reorder the terms: 6 + 3 + 3x = 6x + -3(-4 + x) Combine like terms: 6 + 3 = 9 9 + 3x = 6x + -3(-4 + x) 9 + 3x = 6x + (-4 * -3 + x * -3) 9 + 3x = 6x + (12 + -3x) Reorder the terms: 9 + 3x = 12 + 6x + -3x Combine like terms: 6x + -3x = 3x 9 + 3x = 12 + 3x Add '-3x' to each side of the equation. 9 + 3x + -3x = 12 + 3x + -3x Combine like terms: 3x + -3x = 0 9 + 0 = 12 + 3x + -3x 9 = 12 + 3x + -3x Combine like terms: 3x + -3x = 0 9 = 12 + 0 9 = 12 Solving 9 = 12 Couldn't find a variable to solve for. This equation is invalid, the left and right sides are not equal, therefore there is no solution.
| 7+3x=40 | | 8[3-(2+4x)]-10x=2+3(2-14x) | | 8x-4=5(x+1)+3-9 | | 6-3(2x-8)=12 | | 0.30x+0.30(30)=0.15(82) | | -4(x+6)-x-4=-5(x+3)-13 | | 9x^2-24+16=0 | | x/3-x/2=2 | | -3(4y-7)+2(2y+10)= | | -3y-28=6y+17 | | 4=0.05 | | x^3-20x^2+99x=0 | | .20x-.167x+1=6x | | 6(4x+6)+4=24x+40 | | 8(v+1)-2v=2(3v+1)-10 | | x^3-20x+99x=0 | | x^3-3x^2-49x=-147 | | 3x^2-198-15x=0 | | 2(6-2x)-9x=-.5(-4x+6) | | 4m-8-2m+5=0 | | 0.85x+0.30(100-x)=0.75x | | .25-1=2 | | 9y+-36=-3y | | 5x+11x=96 | | .3(3x-12)=6-2(x-1) | | (x+3)(2-x)(x+4)=0 | | Y+2(y-6)=-2(2y-14)+49 | | x^4-6x^2+1=0 | | -0.9x+7.83=-0.7x+8.23 | | (n+4)*3=30 | | Y+2(y+6)=-2(2y-14)+49 | | 5a+2b-2a-4b= |